Development of the agricultural sector as the major direction of the state financial policy of Kazakhstan. (Journal of actual problems of jurisprudence, 2016)
In the article the author examines the current situation in the agricultural sector as well as development of the agricultural sector as the most important direction of fiscal policy.
Keywords: agricultural sector; agribusiness; and financial policy